Living the Good Life: A Conversation about Well-being, Education, and Culture - Cardinal, Trudy; Lambert, Louise; Lamouche, Sandra (Paideusis, 2015)
In this paper we engage in a conversation speaking from three different perspectives and discuss the ways literature and our personal life experiences can inform policy and practice in relation to the concepts of well-being, education, and culture. We gathered around a metaphorical kitchen table, bringing to it our life experiences, as well as the literature that informed our individual research programs (positive psychology, Indigenous world view, and narrative inquiry) and we began to unpack the questions: “What role does culture play in understanding and educating for well-being and why should an education system be concerned about it?”